Multicentre study to improve clinical interpretation of rheumatoid factor and anti-citrullinated protein/peptide antibodies test results. Issue 1 (23rd March 2022) - Van Hoovels, Lieve; Vander Cruyssen, Bert; Sieghart, Daniela; Bonroy, Carolien; Nagy, Eszter; Pullerits, Rille; Čučnik, Saša; Dahle, Charlotte; Heijnen, Ingmar; Bernasconi, Luca; Benkhadra, Farid; Bogaert, Laura; et al.
Abstract : Background: Rheumatoid factor (RF) and anti-citrullinated protein/peptide antibodies (ACPA) are important biomarkers for diagnosis of rheumatoid arthritis (RA). However, there is poor harmonisation of RF and ACPA assays. The aim of this study was to refine RF and ACPA interpretation across commercial assays. Materials and methods: Six total RF isotype-non-specific assays, 3 RF IgM isotype-specific assays and 9 ACPA immunoglobulin G assays of 13 different companies were evaluated using 398 diagnostic samples from patients with RA and 1073 disease controls. Results: Using cut-offs proposed by the manufacturer, there was a large variability in diagnostic sensitivity and specificity between assays. Thresholds of antibody levels were determined based on predefined specificities and used to define test result intervals. Test result interval-specific likelihood ratios (LRs) were concordant across the different RF and ACPA assays. For all assays, the LR for RA increased with increasing antibody level. Higher LRs were found for ACPA than for RF. ACPA levels associated with LRs >80 were found in a substantial fraction (>22%) of patients with RA. Conclusion: Defining thresholds for antibody levels and assigning test result interval-specific LRs allows alignment of clinical interpretation for all RF and ACPA assays.